Transparency and Accountability for Bequests: The Case of Long Island College Hospital - Lippman, Ellen J.; Teri Grimmer, Teri x (Journal of Leadership, Accountability and Ethics, 2016)
Restricted bequests to not-for-profit organizations can be challenging. Often there is significant lag time between commitment of bequest and death of donor, when operational changes in the beneficiary organization may occur that make adherence to bequest restrictions difficult. Governance systems, external to and within the organization, should exist to monitor the organization’s acceptance and use of bequests. Using the $138 million bequest by Donald and Mildred Othmer to Long Island College Hospital as an example, we consider the stewardship of charitable bequests and the failure of the governance mechanisms in accepting and maintaining bequest restrictions.